Some Cytogenetic Potentials of Vitex negundo Methanolic Extract on MCF-7 Cell Line - Al-Akeedi, Ghofran Laith Hamid; Al Maliky, Worood Kamil Shalash (Journal of Neonatal Surgery, 2025)
Breast cancer has become a common malignancy in most parts of the world. Vitex negundo has been used as a traditional remedy for many diseases. This study investigated the molecular mechanism of breast cancer prevention using breast cancer cell line MCF-7. In this study, an overview of the widely used Vitex negundo plant and its alcoholic, Gas chromatography-mass spectrometry (GC-MS) was used to assess the extract, cell cycle assay and apoptosis by high content screening assay. in GC-MS. The biologically active phytochemical components of the alcoholic extract of the plant were examined. A GC-MS study showed that 27 chemical substances were present. Analysis of the MCF-7 cell life cycle revealed that the plant's alcoholic extract stopped the cell cycle in a concentration-dependent way. Three concentrations—200, 100, and 50 g/ml—were employed. In the highest concentration the cancer cell life cycle was inhibited at sub-G2, whose value increased from 0.56 to 76.8. Thus, the extract prevented the cells from entering the G2 phase, whose value in untreated cells was 22.1 and became 3.51 after treatment with the alcoholic extract. Apoptosis by High-content screening provided an overview of the effects of the alcoholic extract on the cell by measuring a number of parameters. Different concentrations of the extract were tested (200,100,50 and 25 μg/ml ) and the results showed that the highest concentration compared to each viable cell count's untreated cells (VCC) (2222.5+38.8, 3411+162.6), nuclear intensity (NI)(577+11.3, 435+21.2), membrane permeability (CMP)(138.5+26.1 ,95+7.0), mitochondrial membrane permeability (MMP)(361+12.0, 249+33.9), and cytochrome c (Cc)(673.5+10.6, 494+19.7).